The Pharmacokinetics of Triheptanoin and Its Metabolites in Healthy Subjects and Patients With Long‐Chain Fatty Acid Oxidation Disorders. Issue 11 (31st March 2021) - Lee, Sun Ku; Gupta, Manju; Shi, Jack; McKeever, Kathleen
Abstract: Long‐chain fatty acid oxidation disorders (LC‐FAODs) are a group of life‐threatening autosomal recessive disorders caused by defects in nuclear genes encoding mitochondrial enzymes involved in the conversion of dietary long‐chain fatty acids into energy. Triheptanoin is an odd‐carbon, medium‐chain triglyceride consisting of 3 fatty acids with 7 carbons each on a glycerol backbone developed to treat adult and pediatric patients with LC‐FAODs. The pharmacokinetics of triheptanoin and circulating metabolites were explored in healthy subjects and patients with LC‐FAODs using noncompartmental analyses. Systemic exposure to triheptanoin following an oral administration was negligible, as triheptanoin is extensively hydrolyzed to glycerol and heptanoate in the gastrointestinal tract. Multiple peaks for triheptanoin metabolites were observed in the plasma following oral administration of triheptanoin, generally coinciding with the time that meals were served. Heptanoate, the pharmacologically active metabolite of triheptanoin supplementing energy sources in patients with LC‐FAODs, showed the greatest exposure among the metabolites of triheptanoin in human plasma following oral administration of triheptanoin. The exposure of heptanoate was approximately 10‐fold greater than that of beta‐hydroxypentoate, a downstream metabolite of heptanoate. Exposure to triheptanoin metabolites appeared to increase following multiple doses as compared with the single dose, and with the increase in triheptanoin dose levels.